2000
DOI: 10.1074/jbc.275.7.4840
|View full text |Cite
|
Sign up to set email alerts
|

MAN1, an Inner Nuclear Membrane Protein That Shares the LEM Domain with Lamina-associated Polypeptide 2 and Emerin

Abstract: The "MAN antigens" are polypeptides recognized by autoantibodies from a patient with a collagen vascular disease and localized to the nuclear envelope. We now show that one of the human MAN antigens termed MAN1 is a 82.3-kDa protein with an amino-terminal domain followed by two hydrophobic segments and a carboxylterminal tail. The MAN1 gene contains seven proteincoding exons and is assigned to human chromosome 12q14. Its mRNA is approximately 5.5 kilobases and is detected in several different cell types that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
267
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 308 publications
(279 citation statements)
references
References 58 publications
(60 reference statements)
7
267
0
5
Order By: Relevance
“…The MAN1 antigen with an approximate molecular mass of 60 kDa was subsequently identified as laminaassociated polypeptide 2-beta [Lang et al, 1999]. Using ''MAN antiserum'' to screen expression libraries, a partial cDNA for the largest recognized antigen was obtained and isolation of overlapping cDNAs led to the characterization of MAN1 [Lin et al, 2000].…”
Section: Man1: An Intergral Protein Of the Inner Nuclear Membranementioning
confidence: 99%
See 2 more Smart Citations
“…The MAN1 antigen with an approximate molecular mass of 60 kDa was subsequently identified as laminaassociated polypeptide 2-beta [Lang et al, 1999]. Using ''MAN antiserum'' to screen expression libraries, a partial cDNA for the largest recognized antigen was obtained and isolation of overlapping cDNAs led to the characterization of MAN1 [Lin et al, 2000].…”
Section: Man1: An Intergral Protein Of the Inner Nuclear Membranementioning
confidence: 99%
“…The amino-terminal domain preceding the first transmembrane segment contains approximately 450 amino acids and faces the nucleoplasm. The first approximately 50 amino acids of MAN1 is a LEM domain, a helix-loop-helix motif found in lamina-associated polypeptide 2, emerin, MAN1 and several other nuclear proteins [Lin et al, 2000;Cai et al, 2001;Laguri et al, 2001]. The LEM domain has been shown to bind to barrier-to-autointegration factor [Cai et al, 2001].…”
Section: Man1: An Intergral Protein Of the Inner Nuclear Membranementioning
confidence: 99%
See 1 more Smart Citation
“…The outer nuclear membrane is continuous with the endoplasmic reticulum (Franke, 1974), but the inner nuclear membrane associates with the nuclear lamina, a meshwork of intermediate filaments (Aebi et al, 1988), on its nucleoplasmic side. The inner nuclear membrane contains a unique set of membrane proteins, lamin B receptor (LBR) (Worman et al, 1988), LAPs (Foisner and Gerace, 1993), emerin (Manilal et al, 1996), otefin (Ashery et al, 1997), nurim (Rolls et al, 1999), and MAN1 (Lin et al, 2000), which are not present in the outer nuclear membrane or the endoplasmic reticulum.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, genomics itself was inadequate for the identification of NETs. For example, a weak homology "LEM" domain was identified when MAN1 was cloned and sequenced (Lin et al, 2000) because this domain was also found to occur in LAP2 and emerin (hence LEM for LAP2, emerin, and MAN1). However, not all proteins containing LEM domains are concentrated at the NE (Dechat et al, 1998;Raju et al, 2003) and the presence of a LEM domain is not always maintained within a protein family e.g.…”
Section: The Genomics Eramentioning
confidence: 99%